Loss of the histone chaperone ASF1B reduces female reproductive capacity in mice. Issue 5 (May 2016) - Messiaen, S; Guiard, J; Aigueperse, C; Fliniaux, I; Tourpin, S; Barroca, V; Allemand, I; Fouchet, P; Livera, G; Vernet, M
Abstract: Anti-silencing function 1 (ASF1) is an evolutionarily conserved histone H3–H4 chaperone involved in the assembly/disassembly of nucleosome and histone modification. Two paralogous genes, Asf1a and Asf1b, exist in the mouse genome. Asf1a is ubiquitously expressed and its loss causes embryonic lethality. Conversely, Asf1b expression is more restricted and has been less studied. To determine the in vivo function of Asf1b, we generated a Asf1b -deficient mouse line ( Asf1b GT(ROSA-βgeo)437 ) in which expression of the lacZ reporter gene is driven by the Asf1b promoter. Analysis of β -galactosidase activity at early embryonic stages indicated a correlation between Asf1b expression and cell differentiation potential. In the gonads of both male and female, Asf1b expression was specifically detected in the germ cell lineage with a peak expression correlated with meiosis. The viability of Asf1b -null mice suggests that Asf1b is dispensable for mouse development. However, these mice showed reduced reproductive capacity compared with wild-type controls. We present evidence that the timing of meiotic entry and the subsequent gonad development are affected more severely in Asf1b -null female mice than in male mice. In female mice, in addition to subfertility related to altered gamete formation, variable defects compromising the development and/or survival of their offspring were also observed. Altogether, our data indicate the importance of Asf1b expression at the time of meiotic entry, suggesting that chromatin modifications may play a central role in this process.